The myth of the nice girl achieving a career you love without becoming a person you hate - Hauser, Fran. (Boston Houghton Mifflin Harcourt, 2018)
Fran Hauser deconstructs the negative perception of "niceness" that many women struggle with in the business world. If women are nice, they are seen as weak and ineffective, but if they are tough, they are labeled a bitch.
Includes bibliographical references and index.
Keywords: Women--Vocational guidance